(untitled) (Fiep Bulletin - online, 2014)
For the purposes of this research, the Scale of motivation in directing children in sport was conducted, made on the basis of Questionnaire for the evaluation of parents support (Bosnar, 2003), containing ten items. The sample consisted of 300 female students from the Faculty of Teacher Education, University of Zagreb, of which 111 students from pre-school teacher and 189 from school teacher studies. Additionally, the scale of enforced ranks was conducted – ranking according to the importance of different activities in children’s development. Using ANOV A and Mann Whitney U test, differences were determined among students of school and pre-school teacher studies in two items on the scale of motivation in directing children in sport and one difference which refers to the ranking of the art workshop.